Sediment-associated metals levels along the sewer-natural treatment wetland continuum, Phnom Penh, Cambodia. Issue 8 (16th November 2016) - Sereyrath, Lim; Irvine, K.N.; Murphy, T.P.; Wilson, K.
Abstract : Sediment deposited within open sewers of Phnom Penh and the natural wetland that treats the waste was sampled and analyzed by X-ray fluorescence (XRF). Mean levels of Pb, Zn (P < 0.05), and Cu (P = 0.08) were greater in the sewer samples than the wetland, while As was not different (P>0.2), and Mn was greater (P < 0.06) in the wetland. Pb, Cu, and Zn levels generally were lower at the wetland outlet and in quiescent areas, suggesting deposition occurs along the sewer/wetland continuum. Background (natural) levels of Mn and As are higher in soils/sediments of this region and levels in the wetland likely reflect these background levels than enrichment from anthropogenic activity. Although 60% of all metals levels in the wetland samples exceeded USEPA threshold effect concentrations, results of recent studies that analyzed fish and vegetables from the wetland showed a small health risk associated with consumption. The XRF was a good tool for environmental analysis in a developing country.